DOLOMITE FORMATION BY NANOCRYSTAL AGGREGATION IN THE DOLOMIA PRINCIPALE OF THE BRENTA DOLOMITES (NORTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
Upper intra- to supratidal laminites in the Norian Dolomia Principale of the Brenta Dolomites (Northern Italy) commonly consist of aphanitic and partially peloidal dolomite previously interpreted as very early diagenetic or penecontemporaneous. Re-examination of a sample prepared by focused ion beam milling through high-resolution transmission electron microscopy (TEM) revealed that dolomicrite crystals may consist of ca. 5-nm-sized nanocrystals characterized by imperfectly aligned orientation. A similar type of dolomite was found in clay-rich Carnian laminites of the Travenanzes Formation (Venetian Alps, Northern Italy) and was interpreted as indication of primary precipitation. The observation of nanocrystals in both the Dolomia Principale and the Travenanzes Formation allows hypothesizing that dolomite mud formed directly from solution via a non-classical pathway involving nucleation and aggregation of nano-particles. Domains of nanocrystalline dolomite in the Dolomia Principale are embedded within, or cemented by, calcian dolomite showing coherent lattice at the micrometre scale and a modulated structure under the TEM. This new finding provides the first evidence that one of the largest dolomite bodies occurring in the geological record, the Dolomia Principale, commenced with deposition of sediment, consisting of dolomite mud formed from solution via non-classical crystallization, and was partially affected by later pervasive diagenetic dolomitization. Based on these new observations we propose that further nano-scale studies are necessary to substantiate the hypothesis that the formation of large dolomite bodies characterized by abundant dolomicrite may have commenced by non-classical nucleation and growth processes. This approach may provide insight on non-actualistic conditions in ancient environments that may have differed, in their boundary conditions, from their modern analogues.